Association of Frontal Gray Matter Volume and Cerebral Perfusion in Heroin Addiction: A Multimodal Neuroimaging Study - Denier, Niklaus; Schmidt, André; Gerber, Hana; Schmid, Otto; Riecher-Rössler, Anita; Wiesbeck, Gerhard; Huber, Christian G.; Lang, Undine E.; Radue, Ernst-Wilhelm; Walter, Marc; Borgwardt, Stefan (Frontiers in Psychiatry, 2013)
Structure and function in the human healthy brain are closely related. In patients with chronic heroin exposure, brain imaging studies have identified long-lasting changes in gray matter (GM) volume. More recently, we showed that acute application of heroin in dependent pa-tients results in hypoperfusion of fronto-temporal areas compared with the placebo condition. However, the relationship between structural and cerebral blood flow (CBF) changes in heroin addiction has not yet been investigated. Moreover, it is not known whether there is any interaction between the chronic structural changes and the short and long term effects on per-fusion caused by heroin. Using a double-blind, within-subject design, heroin or placebo (saline) was administrated to 15 heroin-dependent patients from a stable heroin-assisted treat-ment program, in order to observe acute short-term effects. Arterial spin labeling (ASL) was used to calculate perfusion quantification maps in both treatment conditions, while Voxel Based Morphometry (VBM) was conducted to calculate regional GM density. VBM and ASL data were used to calculate homologous correlation fields by Biological Parametric Mapping (BPM). We correlated each perfusion condition (heroin and placebo) separately with a VBM sample that was identical for the two treatment conditions. It was assumed that heroin-associated perfusion is manifested in short term effects, while placebo-associated perfusion is more related to long term effects. Correlation analyses revealed a significant positive correlation in frontal and temporal areas between GM and both perfusion conditions (heroin and placebo). The heroin-associated perfusion was also negatively correlated with GM in the left thalamus and right cuneus. These findings indicate that, in heroin-dependent patients, low GM volume is positively associated with low perfusion within fronto-temporal regions.